PROTOTYPE SISTEM PELEPASAN BEBAN BERBASIS INTERNET OF THINGS PADA SISTEM PENYIMPANAN ENERGI GEDUNG TEKNIK ELEKTRO UDAYANA - Sungkono, Gilberth; Dyana Arjana, I Gd.; Setiawan, Widyadi; Maharta Pemayun, A.A Gd. (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p11, 2024)
Solar power plants (PLTS) and wind power plants (PLTB) are plants that utilize renewable energy sources Solar Power Plants and Wind Power Plants that work with an off-grid system will of course utilize batteries to store the energy that has been produced. This research aims to display a prototype that functions as a load shedding system for energy storage. The load shedding control system for microcontroller-based energy storage is designed so that the loading system according to the level of load vitality can be controlled automatically by the system so that manual control is not required. The microcontroller will provide output to the SSR relay will function as a release and connection for the electrical line. This research found results where the use of a load shedding system in energy storage can increase the duration of life of priority load lamps compared to other load classes.